Caracterização geoquímica e paleoambiental do cretáceo inferior da Bacia de Camamu, Bahia - Gonçalves, Félix Thadeu Teixeira (1997)
The Camuru basin is located in the easterns Brazilian continental margin. In this study, 94 rock samples from a single offshore well were submitted to geochemical analyses in order to assess teh depositional paleoenvirenments of the rift sequence from Camamu Basin. Pyrolysis and organic petrograph data suggest and bacterial biomass. Observed variations of the hydrogen and oxygen indices reflect changes from oxic to anoxic conditions of deposition. The integration of palimology and oxygen isotope data indicates climate condictions of increasing aridity and water evaporation (negative water balance) during the deposition of the sediments from Rio da Serra and Aratu stages (local stages), and increasing humidity and water inflow (positive water balance) during the Baraica to Jiquiá stages. The palimnological reconstruction suggests that the Rio da Serra sediments were deposited in a fault-bounded deep lake with fresh to brackish water. Organic preservation was greatly enhanced by the stable water collumn stratification and bottom anoxia. High organic carbon contents and hydrogen indices, together with the strong ¹³C isotopic depletion reflect a medium to low primary productivity and a intense recycling of carbon through the degradation of organic matter by anaerobic bacteria. Aratu and Buracica sediments were deposited in a broad and shalower lake with fresh to saline water. The high organic carbon contents and the strong 13C isotopic enrichment is interpreted as the results of the enhancement of primary productive due to increased input and recycling of nutrients favoured by the lake morphology and a humid climate.